Do you mean...

\(24x^2+25x-47ax-2=-8x-3-53ax-2\) and it's true for all values of \(x\) that's not 2 , solve for \(a\) ? It's kind of hard with your format, but...

That equals \(24x^2+33x+6ax=0\) and we can factor this: \(x(24x+6a+33)=0\)

Since \(x\) is not 2, let's plug in 2 to see what we can exclude!

\(2(24\times 2+6a+33)=2(48+6a+33)=2(81+6a)\) and if that equals zero then \(a=-\frac{81}{6}\)

However, that's not one of the answer choices so none of the answer choices work.

That's what I think, but your formatting was not very clear, is it ok if you make it a bit neater? Thanks ;)

You are very welcome!

:P